A Magyar Távirati Iroda közleménye Benárd Ágoston nyugalmazott miniszter népbírósági ítéletéről : 1948. október 7. - Vizi, László Tamás (Közép-Európai Közlemények, 2012)
In the 7th October 1948. the Hungarian News Agency reported in a brief report that the National Council of People’s Court convicted for six year long prison sentence Dr. Ágost Benárd, former „fascist” Minister of Labor and Social Welfare (1920–1921). The charges against Mr. Benard were: in 1900-1901 he was initiated at the unfolding of the riots and fighting on the Budapest University; he made inflammatory speeches against the left party as a parliament representative; he was member of anti-democratic associations; as the editor in chief of the newspaper of „A Nép” he gave place for inflammatory articles; in 1944, in Wien he entered the SS and he was on duty in it. This study does not undertake to full detailed explore the Benard-trial. It only would like to compare the information of the Hungarian News Agency with the facts. Pointing out, that the trial against Mr. Benard was aimed to condemn the Christian social ideas. The Benard-trial can be interpreted as the overture and rehearsal of the attacks against the Christian Church. The study points on the conceptual nature of the trial, thus it raises the need of revision in Ágost Benárd’s case.